EFEK ANALGESIK FRAKSI ETANOL DARI EKSTRAK ETANOL DAUN MINDI (Melia azedarach L.) PADA MENCIT JANTAN - Indah Purwantini,; Purwantiningsih Purwantiningsih; Oktavia Eka Puspita (Jurnal Ilmiah Farmasi, 2007)
ABSTRACTIndonesia has a lot of traditional medicines, which people used long time ago, one of theseis mindi (Melia azedarach L.). It have been known that ethanolic extract of mindi leaves hasanalgesic effect greater than paracetamol at dose 6.44 mg/kgBW and 12.89 mg/kgBW. Thisresearch conducted to find out the effectiveness ethanolic fraction of ethanolic extract as ananalgesic. The research was carried out in completely random one way design, used 35 micewhich have been fasted for 24 hours. The mice were divided into 7 groups i.e. negative control,positive control and 5 testing groups (in different doses). Fifteen minutes after injected with thefractions of mindi, the mice were given acetic acid 0.5% intraperitoneally injection. The cumulativewrithe reflects were calculated in every 5 minutes for one hour and were counted the protectionpercentage. Results showed that the ethanol fractions doses 12,88-103,04 mg/kgBW of mindileaves have the analgesic effect in mice and gave protection percentage 30.93-71.61%. Thechromatograms of TLC indicated that the fraction contain flavonoids and phenolic compounds.Key words: ethanol fraction of mindi, analgesic effect, TLC profile